2017
DOI: 10.1177/0961203317692432
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy failure in patients with obstetric antiphospholipid syndrome with conventional treatment: the influence of a triple positive antibody profile

Abstract: Conventional treatment of obstetric antiphospholipid syndrome fails in approximately 20-30% of pregnant women without any clearly identified risk factor. It is important to identify risk factors that are associated with these treatment failures. This study aimed to assess the impact of risk factors on pregnancy outcomes in women with obstetric antiphospholipid syndrome treated with conventional treatment. We carefully retrospectively selected 106 pregnancies in women with obstetric antiphospholipid syndrome tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 27 publications
3
35
1
1
Order By: Relevance
“…The present finding that antibody composition did not represent a risk factor for specific adverse pregnancy outcomes among women with APS was also inconsistent with previous research . Several studies have suggested that antibody composition—primarily the triple‐positive profile—increases the risk of adverse pregnancy outcomes, even when women with APS receive appropriate treatment . The present study included only one patient who tested positive for all three autoantibodies; therefore, the effect of the triple‐positive profile could not be assessed.…”
Section: Discussioncontrasting
confidence: 98%
See 2 more Smart Citations
“…The present finding that antibody composition did not represent a risk factor for specific adverse pregnancy outcomes among women with APS was also inconsistent with previous research . Several studies have suggested that antibody composition—primarily the triple‐positive profile—increases the risk of adverse pregnancy outcomes, even when women with APS receive appropriate treatment . The present study included only one patient who tested positive for all three autoantibodies; therefore, the effect of the triple‐positive profile could not be assessed.…”
Section: Discussioncontrasting
confidence: 98%
“…These investigators used a composite outcome of fetal or neonatal loss, preterm delivery (≤32 weeks), and FGR. Latino et al . described the presence of high‐titer aβ2GP as a risk factor for adverse events, especially pregnancy loss.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[17] The association of several antibody titer with pregnancy outcomes in APS women has further been shown. [18,19]…”
Section: Discussionmentioning
confidence: 99%
“…Yapılan araştırmalarda antifosfolipidantikorlarının pozitifliği obstetrik komplikasyonların artışı ile ilişkili olduğu gösterilmiştir (15)(16)(17). Antifosfolipid antikor sendromu obstetrik fetal ölüm ve rekurren abortuslara neden olmaktadır (18).…”
Section: Yöntemunclassified